Law Enforcement Against Influencers (Artists, Youtubers, and Celebgrams) Who Promote Online Gambling Sites - Luthfi Mohamad Ashar (UM Purwokerto Press, 2023)
The development of technology in the current era of globalization continues to develop in facilitating human life to carry out daily activities. With the rapid development of technology, it is easier to interact on the internet, namely social media. The existence of social media such as YouTube and Instagram causes many new celebrities and YouTubers to emerge, with many followers on Instagram and YouTube platforms causing offers from online gambling sites to promote with large enough rewards so that they become tempted to promote. This research determines the formulation of the problem, namely how legal action against Influencers (artists, youtubers, celebrities) who promote online gambling sites and What obstacles Law Enforcement Faces in Combating Influencers who promote Online Gambling Sites. The purpose of this research is to provide a deterrent effect to actors including public figures who promote or advertise on their social media platforms and prevent and minimize the emergence of new actors either playing or owning online gambling site platforms. This research is analyzed using normative juridical research methods, in order to use this research to provide law enforcement to influencers who promote online gambling sites because there are still many freely promoting them.